KONSEP PENGEMBANGAN EKOWISATA GARAM MELALUI PENDEKATAN TRIPLE HELIX DI PULAU MADURA - Triana Setiyarini; Yustina Chrismardani (Universitas Trunojoyo Madura, 2019)
Madura Island has long been known as a salt island. Alt hough there are many tourist destinat ions in Madura, no one hasutilized and developed salt as an ecotourism potent ial. Throughsalt ecotourism, it is expected to be a solution to some of theproblems associated with salt, especially to improve the welfareof salt farmers. The purpose of this study was to determine theconcept of salt ecotourism development through the triple helixapproach on Madura Island. This type of research is induct iveanalysis by collect ing, compiling and describing various actualdata, documents and informat ion. The data that has beenobtained is then analyzed by descriptive analysis method. Theresults showed that the potential for salt cult ivation in fourdistricts in Madura namely Bangkalan, Sampang, Pamekasanand Sumenep can be used as an opportunit y to develop attractivetourism through the concept of salt ecotourism. This is becauseMadura's land could meet five basic principles of ecotourismdevelopment in Indonesia, namely the principles ofconservation, educat ion, tourism, economy, and participat ion oflocal communit ies. Salt ecotourism requires collaboration fromacademics, businesses represented by groups of salt farmers, andthe government. These three actors, called triple helix, havedifferent roles in order to develop salt ecotourism starting fromplanning, utilizat ion and control.